DINAMIKA MASYARAKAT LOKAL DI PERBATASAN - Zaenuddin Hudi Prasojo (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
Community members living in borderland areas in Indonesia tended to be clasified as under-developed society in development aspects. Study on the borderland areas is still limited both in quantity and the impact of the study. Nanga Badau located in borderland between West Kalimantan (Indonesia) and Serawak (Malaysia) is one of the under-developed borderland area. This paper revealed the dynamic issues and the existence of local tradition in the context of globalization. It was showed that the original attitude of warn, friendly, and respect visitors express their openess toward global trend but still keep on local style. They are also realized on their position among global community. The open access abroad effected in the development of the interaction, information, and communication patterns among Iban Dayak. Sophisticated devices like mobile phone and television are familiar among Iban dayak in borderland area.